The inflammatory effects of diet, nutritional status, and severity of chronic kidney disease at Bogor City Hospital - Ade Hikmah; Mira Dewi; Cesilia Meti Dwiriani; Erwindo Rinaldo (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Diet and nutritional status play an important role in chronic kidney disease (CKD). Pro-inflammatory foods are linked to a decline in kidney function, whereas the nutritional status of obesity is a risk factor for CKD. This study aimed to analyze the relationship between (DII), nutritional status, and CKD severity. This cross-sectional study was conducted between April and May 2023 at Bogor City Hospital. A total of 64 patients with CKD were selected using accidental sampling. Consumption data were collected from the SQ-FFQ, nutritional status was assessed using Body Mass Index (BMI), and disease severity was assessed using creatinine and estimated glomerular filtration rate (eGFR) levels. Data were analyzed using ANOVA, Kruskal-Wallis, Pearson, and Spearman correlation tests. Results: All subjects had positive DII scores, their nutritional status was mostly in the normal range (59,4%), and almost all subjects had CKD stage 5 (95,3%). No relationships were found between the DII score and creatinine level (p= 0,986) and eGFR (p= 0,359). There was also no relationship between nutritional status and creatinine (p= 0,985 ) and eGFR (0,442). In conclusion, a positive DII score indicated that all subjects consumed more pro-inflammatory foods. Actions are needed to get CKD patients with CKD who consume more anti-inflammatory foods.